THE ACTIVITIES OF UGTU BUSINESS INCUBATOR IN SHAPING THE IMAGE OF THE UNIVERSITY - Andrey G. Pulkin; V. A. Pulkina (Высшее образование в России)
The article highlights the activity of business-incubator UGTU in the context of forming the image of the university. The potential for optimization of university's image elements through the communication work with various target audiences of the university is covered. The article describes the university "s image elements such as the image of educational services, students' image, internal image of the organization, university rector "s image, the image of teaching staff and personnel, the social image of the organization, the visual image of the organization, business organization"s image through the prism of education and information activities of the business incubator. The purpose of the article is to reveal the role of such a university structure in maintaining its positive image.